Physical Education for the Treatment of Height Defects in Children (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article highlights the importance of physical education exercises in the treatment of height defects in children, as well as the defect (physical defect) of height changes - the shoulder arches of the body, the changed position of the pelvis and head, and the changes in the physiological curvature of the spine. given In the formation of the figure, the spine and the iliac bone are of great importance, as well as the individual measurements of the isthmus, height, weight, the level of muscle development, and the activity of subcutaneous fat.